Phylogenomic insights into LA-MRSA from Argentine pig farm environments: novel OptrA variant and regional emergence of an ST9 lineage co-circulating with international CC398 lineages - González, María José; Parada, Julián; Blasko, Enrique; Sosa, Ezequiel Jorge; Suleyman, Geehan; Kaur, Jagjeet; Maki, Gina; Prentiss, Tyler; Corti Isgro, Maite; Pereyra, Natalia; González, Rocío; Dagatti, Agostina; et al. (Frontiers in Microbiology, 2025)
IntroductionStaphylococcus aureus (SA) colonizes both humans and animals. The spread of livestock-associated methicillin-resistant S. aureus (LA-MRSA) in farms and the environment poses a public health concern. While CC398 is globally predominant, regional variation exists, and data from Argentina remain scarce. This study investigated the presence, antimicrobial resistance (AMR), and genomic features of pig-associated MRSA in central Argentina, including transmission dynamics and the global phylogenetic context of LA-MRSA lineages CC398 and CC1/ST9.MethodsBetween February and March 2022, 41 MRSA isolates were recovered from 50 fecal and effluent samples collected from 8 of 10 (80%) farrow-to-finish pig farms in Córdoba province, Argentina. Phenotypic susceptibility was assessed by disk diffusion and Vitek2 (CLSI 2023). Genotypic characterization included PCR for antimicrobial resistance genes (ARGs) and the immune evasion cluster (IEC), as well as PFGE, spa typing, SCCmec typing, and MLST. Twenty-four isolates underwent whole-genome sequencing (Illumina NovaSeq 6000) for resistome, virulome, and phylogenomic analysis.ResultsAntimicrobial use was extensive, with most farms reporting use of more than seven drug classes and up to 18 compounds in the previous six months. Two predominant IEC¯ LA-MRSA lineages were identified, mostly associated to SCCmecV: CC398 (53.7%, n:22), comprising ST398 (n:17, spa-types t034/t571) and ST8814 (n:5, t571); and CC1/ST9 (41.5%, n:17, spa-t16964). One IEC+ CA-MRSA lineage (CC8/ST72, n:2, SCCmecIVa) was also detected. All isolates were multidrug-resistant (MDR), with LA-MRSA showing broader resistance across 4–7 antimicrobial classes. Multiple ARGs matched phenotypic resistance, except optrA, found in ST398 (n:5) and ST9 (n:1) despite borderline linezolid MICs (2–4 µg/mL), representing the first report of optrA in S. aureus in Argentina. WGS revealed a novel optrA variant (OptrA/FDKFP), likely linked to a mobile genetic element. Phylogenetic analysis revealed the local emergence of a distinct ST9 clade and multiple introductions of CC398 within internationally recognized subgroups (C6/AAP and C6/EP4).DiscussionThese findings underscore pig farms as emerging reservoirs of multidrug-resistant MRSA both locally and globally, reinforcing the need for targeted surveillance and control strategies at the animal–human interface.